Analysis Of Work Climate And The Increase Of Blood Pressure Of Construction Workers In Pamekasan Regency - Dzul Fahmi Afriyanto1 , Noeroel Widajati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The excessive exposure of work climate can cause health problems to workers. One of the problems is a change in physiological response in the form of increased blood pressure. The purpose of this study is to determine the relationship between the work climate and the increase of blood pressure in construction workers in Pamekasan Regency. This study is a descriptive observational study with a cross sectional design. The contingency coefficient correlation test was used to analyze and determine the relationship of the variables. The subjects were 19 construction workers in Pamekasan Regency, East Java, Indonesia drawn from the population according to the specified criteria. To collect the data, several different instruments were used. Questtemp 36 was used to measure the workclimate, direct observation with the standard of SNI 7269-2009 was carried out to assess the physical workload and sphygmomanometer was used to measure the blood pressure. The blood pressure measurement was carried out the someone with the medical competence. The result of work climate exposure showed that most of workers (84.3%) were exposed to beyond-threshold-value work climate. The results of blood pressure measurement showed that (36.8%) workers showed abnormal blood pressure. The statistical analysis for the correlation of work climate and the increase in blood pressure showed a moderate correlation with the contingency coefficient value of 0.314. It is recommended for companies in this construction project to add blower fan to the working areas where the work climate exceeds the threshold limit value (TLV) as well as at workers’ resting places. In addition, companies are suggested to hold periodic health checks, especially routine blood pressure checks.